2005
DOI: 10.1167/iovs.04-0776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cholesterol-Lowering Statins on the Aqueous Humor Outflow Pathway

Abstract: This study demonstrates that the statin drugs lovastatin and compactin induce changes in cell shape and actin cytoskeletal organization and decrease MLC phosphorylation in PTM and PCB cells, all of which are events that are likely to lead to cellular and tissue relaxation. In addition, these effects of the statins appear to be mediated by inhibition of isoprenylation of the small GTP-binding proteins such as Rho GTPase. An important finding is that statins exert an ocular hypotensive response in an organ-cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 50 publications
2
60
1
4
Order By: Relevance
“…Porcine TM cells were isolated by collagenase as described previously. 23 Porcine TM cells were cultured in Dulbecco's modified Eagle medium (DMEM; WAKO Pure Chemical Industries, Osaka, Japan) containing 10% fetal bovine serum (FBS; Hyclone Laboratories, Logan, UT), 2 mM glutamine, 100 U/mL penicillin, 100 lg/mL streptomycin, and 0.5 lg/mL amphotericin B at 378C in 5% CO 2 , and TM cells between passages 3 and 5 were used for all the experiments in our study.…”
Section: Cell Culturementioning
confidence: 99%
“…Porcine TM cells were isolated by collagenase as described previously. 23 Porcine TM cells were cultured in Dulbecco's modified Eagle medium (DMEM; WAKO Pure Chemical Industries, Osaka, Japan) containing 10% fetal bovine serum (FBS; Hyclone Laboratories, Logan, UT), 2 mM glutamine, 100 U/mL penicillin, 100 lg/mL streptomycin, and 0.5 lg/mL amphotericin B at 378C in 5% CO 2 , and TM cells between passages 3 and 5 were used for all the experiments in our study.…”
Section: Cell Culturementioning
confidence: 99%
“…Although the applicability of statins on age-related macular degeneration is still under investigation (49), statins are shown to have protective effects on primary open-angle glaucoma, a major cause of blindness (50). The regulation of the intraocular pressure (IOP) within a physiological range is of great clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the intraocular pressure (IOP) within a physiological range is of great clinical importance. Statins are reported to downregulate the IOP by increasing aqueous humor outflow via the inhibition of Rho/Rho-kinase pathway in the trabecular meshwork and the ciliary body (50).…”
Section: Discussionmentioning
confidence: 99%
“…Similar fi ndings of the statin-induced MLC dephosphorylation have been reported in other cell types, including vascular endothelium. 9,39,40 In our recent study, we have also observed that microtubule disassembly induced by thrombin can be suppressed by pretreatment with paclitaxel, a microtubule stabilizing agent. 41 Similar barrier dysfunction involving microtubule disassembly is well known in vascular endothelium as well.…”
Section: Effect Of Lovastatin On Status Of Mypt1 Phosphorylationmentioning
confidence: 85%